Image Methods, Verbal Symbolism, Demonstrations And Visuals In The Texter Of The Qur'an - Asep Saepulloh; Fitry Liana; Tatang Abdul Basir; Mastuhi Mastuhi (Universitas Muhammadiyah Enrekang, 2022)
The Qur'an was sent down to understand the instructions for humans towards clear goals and straight paths by upholding the principles of life based on faith. The purpose of this study is to analyze the method of interpreting the Qur'an by parable, verbal symbolism, demonstrations, and visuals in the Qur'an. The research method used is library research. The results of the study show that Majaz is using lafadz to mean something other than the original meaning because it has something to do with the original meaning and there is a qorinah that points to it. For example, using the word